Study Of Mangrove Vegetation In The Kasih Sayang Mangrove Zone Area, Mundu Coastal Village, Mundu District, Cirebon Regency - Elinah, Elinah; Khaerudin, Rizky Brehnaputrifajar; Nurlaeli, Nurlaeli (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2023)
Cirebon is one of the coastal areas that has very potential mangrove areas. The existence of mangroves in this area has an important role for the survival of other ecosystems, but the type of mangrove vegetation has not yet been identified. The aim of this research is to determine the type of mangrove vegetation in one of the coastal areas of Cirebon Regency, namely in the Kasih Sayang Mangrove Zone, Mundu Pesisir Village. Importance values, relative density, relative frequency, and relative dominance obtained from vegetation analysis are used as indicators to describe the structure of mangrove vegetation. To support this research, water quality measurements (temperature, pH, dissolved oxygen and salinity) were carried out in situ in mangrove forests. This research was conducted from July to August 2023. This research was conducted using the Purposive Sampling method. The research results show that there are 4 types of mangroves, namely Rhizopora mucronata, Bruguiera, Xylocarpus Granatum, and Avicennia marina. Based on the importance value analysis, it shows that the Rhizopora mucronata species has the highest importance value compared to other species, namely 154.17%. The condition of water quality in the Mundu Coast, Cirebon district, is still considered adequate to support the life and development of mangroves.